Magnolia essential oil: a preliminary exploration of chemical composition and its antimicrobial and antioxidant potential - Liu, Yingjie; Han, Ningling; Meng, Fanxin (Frontiers in Microbiology, 2025)
In this study, the chemical composition of Magnolia essential oil (MEO) was analyzed using gas chromatography-mass spectrometry (GC-MS). The results indicated that terpenoids were the primary constituents, with the main components being 1,8-cineole (44.87%), (+)-citronellal (6.93%), and linalool (29.1%). The antibacterial activity of MEO against four target bacteria was confirmed through inhibition zone assays, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) tests. The bacterial growth curve demonstrated that MEO significantly inhibited bacterial growth and effectively delayed the logarithmic growth phase. Mechanistic studies suggested that MEO primarily acts in the initial stages of bacterial growth by disrupting the bacterial cell membrane, leading to substantial leakage of intracellular materials, impairing metabolic activities, inducing lipid peroxidation, and enhancing oxidative stress, thereby inhibiting normal bacterial proliferation. Furthermore, MEO’s antioxidant properties were evaluated through its scavenging effects on DPPH and hydroxyl radicals, as well as its ferric reducing antioxidant power (FRAP). The findings revealed that MEO exhibited the strongest scavenging activity against DPPH radicals, followed by hydroxyl radical scavenging, with the FRAP results being comparatively weaker. These results suggest that MEO not only possesses potent antibacterial effects but also exhibits notable antioxidant activity, indicating potential for broader applications.